The Effect of Employee Welfare and Job Satisfaction on Employee Performance At CV. Media Utama Group Pangarengan Sampang. - muzanni, Ach; Wildan, Muhammad Alkirom (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
CV. Media Utama Group is a company engaged in the production of salt, in the midst of very tight competition CV. Media Utama Group is determined and strengthens its commitment by improving the performance of employees in its company. This study analyzes the effect of employee welfare and job satisfaction on employee performance. The independent variable in this study is employee welfare, job satisfaction and the dependent variable is performance. This study uses a quantitative approach, with an analytic observational type. The data collection method used a questionnaire and analyzed the data using multiple linear regression. The purpose of this study was to determine whether the level of employee welfare has an effect on employee performance at CV. Media Utama Group pangarengan  Sampang and to find out whether job satisfaction has an effect on employee performance at CV.  Media Utama  Group  pangarengan Sampang. Based on the results of the analysis of this study, it shows that employee welfare and job satisfaction have a positive and significant effect on employee performance at CV. Main Media Group Pangarengan Sampang. Employee Welfare has a positive and significant effect on employee performance CV. Main Media Group Pangarengan Sampang amounted to (β) 0.413 with a tcount value of 2,9311,678 and a significance value of 0.0050.05. Job Satisfaction has a positive and significant effect on employee performance CV. Main Media Group Pangarengan Sampang of (β) 0.609 with a tcount of 3.2671.678 and a significance value of 0.0020.05.